2018
DOI: 10.14295/cs.v9i3.1389
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic efficiency of ‘Cantaloupe’ melon under different water blades and organic fertilization

Abstract: The objective of this study was to evaluate the effect of different irrigation blades on the presence and absence of biofertilizer on the agronomic performance of the ‘Cantaloupe’ melon in the Paraíba backwoods. The work was conducted under field conditions in the Agroecology Sector, belonging to the State University of Paraíba (UEPB), Campus IV. The experimental design was a randomized block using four irrigation blades (60, 80, 100 and 120% - ET0, (mm day-1)) with presence and absence of biofertilizer replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…Souza et al, (2018) when studying melon plants submitted to mineral fertilization and organic fertilization, both combined and used separately, the dry matter yield of leaves, stems, fruits and shoots of melon plants was not affected, however, the application of bovine manure increased the availability of the organic forms of nitrogen in the soil. Similarly, Irineu et al (2018) observed a significant effect on the application of enriched bovine biofertilizer, on the number of seeds and weight of 100 seeds, attributing these gains the availability of nutrients supplied to the soil by the biofertilizer, as well as the adequate supply of the plants.…”
Section: Resultsmentioning
confidence: 90%
“…Souza et al, (2018) when studying melon plants submitted to mineral fertilization and organic fertilization, both combined and used separately, the dry matter yield of leaves, stems, fruits and shoots of melon plants was not affected, however, the application of bovine manure increased the availability of the organic forms of nitrogen in the soil. Similarly, Irineu et al (2018) observed a significant effect on the application of enriched bovine biofertilizer, on the number of seeds and weight of 100 seeds, attributing these gains the availability of nutrients supplied to the soil by the biofertilizer, as well as the adequate supply of the plants.…”
Section: Resultsmentioning
confidence: 90%
“…(Santos et al 2014) who studied the nutrition of pineapple crown sprouts, (Silva et al 2014), who studied the decomposition and release of nutrients from organic sources, and (Irineu et al 2018) studied the application of organic fertilizer in melons. Studies have shown the benefits of using organic fertilizers for crop growing, such as poultry litter in pineapple (Pereira et al 2019), humic acids in pineapple crown sprouts (Santos et al 2014), and biofertilizer based on bovine manure in melons (Irineu et al 2018). The decomposition and nutrient release from poultry little and cattle manure have also been studied (Silva et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the last decades, organic fertilization has also been used as an economic and environmental alternative, in the partial or total replacement of chemical fertilizers. Besides releasing nutrients necessary for plant growth, organic fertilizers provide benefits to the soil, such as improvements in structure, aeration and moisture storage capacity, regulating the effect in temperature and cation exchange capacity, which, in turn, potentiates crop productivity [10,11].…”
Section: Introductionmentioning
confidence: 99%